FORECASTING BUDGETING ANALYSIS IN EVALUATING THE COMPANY’S FEASIBILITY IN MARKETING PROSPECTS - Ayu , Nabilla Sekar; Nurdiansyah, Dian Hakip (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The purpose of this study is to determine three forecasting methods that can be used based on historical data forecasting chart patterns, determine the method accurate forecasting with the smallest error rate based on the three methods on product demand. The results of the research obtained are the forecasting graph which has a horizontal pattern due to fluctuations in values around the average, the forecasting calculation is it is known that there are three methods used, namely; Method Exponential, Exponential Smoothing with = 0.1 and Exponential Smoothing with = 0.2 So that The most appropriate method is used in analyzing the data with the highest error rate the smallest of the three methods used in the Atap H product for the January 2019 forecast, namely using the Exponential Smoothing Method with = 0.2 with a MAPE value of 72.962; MAD i.e 666,999.17; MSE is 444,887,888,334.03; and MFE which is 666,999.17.